1984
DOI: 10.2307/1510483
|View full text |Cite
|
Sign up to set email alerts
|

Academic and Behavioral Characteristics of Learning Disabled Children and Average Achievers: Longitudinal Studies

Abstract: Longitudinal research in the area of learning disabilities has been lacking for some time. The study reported here is an attempt to chart the development of newly identified LD children over the early elementary school years while they are receiving LD services in the public school. This paper includes initial behavioral and academic data for a large sample of 6- and 7-year-old LD and normally achieving students, and charts the progress of about half the children over a 3-year period using teacher rating scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
43
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 14 publications
6
43
0
Order By: Relevance
“…These findings are very consistent with those from several prior studies in which parallel or slightly converging growth curves have been observed for better and poorer readers (Baker et al, 1984;Jordan et al, 2002;Phillips et al, 2002;Shaywitz et al, 1995). Such results are in disagreement, however, with those of several studies in which divergence between LD and NLD groups has been seen over time for at least some kinds of reading abilities (Juel, 1988;McKinney & Feagans, 1984;Bast & Reitsma, 1998). Several explanations for the disparate findings merit consideration.…”
Section: Matthew Effectssupporting
confidence: 85%
See 3 more Smart Citations
“…These findings are very consistent with those from several prior studies in which parallel or slightly converging growth curves have been observed for better and poorer readers (Baker et al, 1984;Jordan et al, 2002;Phillips et al, 2002;Shaywitz et al, 1995). Such results are in disagreement, however, with those of several studies in which divergence between LD and NLD groups has been seen over time for at least some kinds of reading abilities (Juel, 1988;McKinney & Feagans, 1984;Bast & Reitsma, 1998). Several explanations for the disparate findings merit consideration.…”
Section: Matthew Effectssupporting
confidence: 85%
“…In the present analyses, however, we used the same test as Shaywitz et al did, and our results for individual reading subtests mirrored those for the composite score. Moreover, the lack of group x grade x subtest interactions in our analyses, and the equivalent results for word recognition and reading comprehension in other studies using a variety of tests (Baker et al, 1984;Catts et al, 2003;Jordan et al, 2002;McKinney & Feagans, 1984), suggests that whether Matthew effects were observed cannot be attributed to the kind of reading measure(s) that different researchers have examined.…”
Section: Matthew Effectsmentioning
confidence: 46%
See 2 more Smart Citations
“…These findings are aligned with previous longitudinal studies that included a non-LD comparison group. Here, researchers (McKinney & Feagans, 1984) reported declining scores on word recognition and reading comprehension with increased time spent in the resource-room setting. …”
mentioning
confidence: 78%